Swallowing and nutritional characteristics of patients with post-covid-19 syndrome: ambispective study - Arteaga, Erica Andrea Veja (2025)
The objective of this study was to describe the swallowing profile through clinical and instrumental assessments and the nutritional profile of patients with post-COVID-19 syndrome, stratified by sex. This was an ambispective study. Primary data collection was conducted at the Post-COVID-19 Rehabilitation Outpatient Clinic of a university hospital, selecting 50 adult individuals who had been hospitalized for severe COVID-19. All participants underwent swallowing assessments (Eating Assessment Tool-10 – EAT-10; Volume-Viscosity Swallowing Test – V-VST; and Fiberoptic Endoscopic Evaluation of Swallowing – FEES) and nutritional evaluations (Mini Nutritional Assessment – MNA and Body Mass Index – BMI). The study included 26 women (51.04 ± 13.59 years) and 24 men (55.92 ± 10.18 years) assessed four months after acute COVID-19 infection, with a history of prolonged intensive care unit (ICU) hospitalization for more than 20 days. Swallowing alterations in females and males were identified through EAT-10 (53.85% vs. 8.33%; p=0.001), V-VST (76.92% vs. 79.17%; p=0.848), and FEES (92.31% vs. 83.33%; p=0.651), respectively. Both women (35.41 ± 5.68 kg/m²) and men (31.65 ± 4.64 kg/m²) were classified as obese. Nutritional risk, as assessed by the MNA, was observed in both sexes (53.85% of women and 58.33% of men), with 23.08% of women classified as malnourished. No correlations were observed between swallowing variables and BMI classification or MNA scores. Our results suggest that individuals with post-COVID-19 syndrome are at risk for dysphagia and obesity, regardless of sex. Furthermore, malnutrition was more prevalent among women. These findings highlight the importance of timely management of swallowing and nutritional disorders to assess and optimize rehabilitation, preventing associated sequelae.